Laporan Penelitian Pengaruh Motivasi, Stress, dan Self-Reward Mahasiswa terhadap Pembelajaran Blended Learning di Perguruan Tinggi Kota Salatiga - Wijayanto, Dwi (Peneliti.net, 2023)
Education is a pillar in life. Education can be pursued both academically and non-academically. Motivation is a basic human drive that drives behavior so that is influences the student learning process. Stress occurs there is a discrepeancy between expectations and reality that effects student in learning. Whereas Self-Reward is behavior that results from actions such as when a student has finished learning in college academic environment. The problem that will be examined is how the influence of motivation, stress, and student self-rewards on learning Blended Method on tertiary institutions. The purpose of this study is to examine how Motivation, Stress, and Self-Reward as mediation of Blended Learning in Higher Education students in Salatiga Town. The important thing from this research is that it can expedite the college’s activities in facing the new normal order after the Covid-19 pandemic hit Indonesia. This research was conducted on active students of Sekolah Tinggi Ilmu Ekonomi AMA Salatiga, based on a population of 1.253 students. Sampling in this study using data collection through a questionnaire. This research is a quantitative, qualitative and descriptive research using survey and literature methods. Questionnaires were distributed via electronic platforms with total 100 respondents who were distributed via social media